COMPARATIVE EVALUATION OF AMISULPRIDE AND ESCITALOPRAM ON SHEEHAN’S DISABILITY SCALE AMONG DEPRESSION PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL IN NEPAL - Kaul, Vijay; Dutta, Shaktibala; Beg, Mirza Atif; Singh, Nand Kishore; Bawa, Shalu; Anjoom, Mohammad; Dutta, Srihari (Journal of Drug Delivery and Therapeutics, 2015)
Introduction and Aim: Depression is an important global public health problem due to its relatively high lifetime prevalence and significant disability caused by it. The present study was conducted to compare improvement in functional outcome by Amisulpride and Escitalopram among depression patients using Sheehan’s Disability Scaling. Material and methods: The study was conducted in depression patients for 1 year in the Department of Neuropsychiatry, Nepalgunj Medical College & Teaching Hospital. A total of 117 depression patients were divided into 2 groups. Group I (58 patients) received Amisulpride tablet at a dose of 50 mg/day and Group II (59 patients) were given Escitalopram at a dose of 10 mg/day. The patients were required to follow up at 4, 8 and 15 weeks. The efficacy of the drugs was calculated by Hamilton depression rating scale (HAM-D). The improvement in functional outcome was compared between the two groups by using Sheehan’s Disability Scale (SDS). Appropriate statistical tools using GraphPadInstat 3.0 were used for analysis. p value < 0.05 was considered significant. Results: HAM-D score in group receiving Amisulpride at 0 and 15 weeks was 16.92±0.35 and 7.87±0.29 (p<0.0001). HAM-D score in group receiving Escitalopram at 0 and 15 weeks was 17.09±0.39 and 6.63±0.39 (p<0.0001). Sheehan’s Disability Score in group receiving Amisulpride at 0 and 15 weeks was 20.35±0.31 and 11.08±0.60 (p<0.0001). SDS score in group receiving Escitalopram at 0 and 15 weeks was 21.53±0.55 and 11.49±0.46 (p<0.0001). Intergroup comparison at 15 weeks was insignificant (p>0.05). Gastrointestinal disturbances, sexual disturbances, amenorrhea, lactation, agitation and insomnia were the commonly encountered adverse drug reactions. Conclusion: Both Amisulpride and Escitalopram showed improvement in Sheehan’s Disability Scale at the end of study period. But intergroup comparison showed no significant difference in the two groups. Key words: Depression, Amisulpride, Escitalopram, Sheehan’s Disability Scale (SDS).